Application of therapeutic physical exercises and massage in treatment and rehabilitation of patients with muscular torticollis - Samosiuk, I.; Kopchak, S.; Chudnaja, R.; Degtyarev, Yu.; Slautenko, N.; Zukow, W. (Journal of Education, Health and Sport, 2011)
The paper presents recommendations for the use of physical exercises and massage in the treatment and rehabilitation of patients with muscular torticollis. Recommendations are intended for surgeons, doctors and exercise instructors with higher and secondary education, massage therapists and paediatricians hospitals and clinics.